(untitled) (Early Childhood Education & Parenting (ECEPA), 2025)
This study aims to analyze the learning management at KB-TK Anak Cerdas Ungaran. The subjects of the research are the principal and teachers. Data were collected using qualitative research methods, including subject selection, research location, and data analysis techniques. The findings of the study reveal the processes of learning planning, implementation, and assessment. The results indicate that learning planning, implementation, and assessment at KB-TK Anak Cerdas Ungaran have been carried out effectively. In the aspect of planning, KB-TK Anak Cerdas Ungaran develops annual activity programs, commonly referred to as the Annual Program (PROTA). The planning process involves meetings and discussions between the principal and the teaching staff to ensure the achievement of children’s developmental goals. In the implementation of learning, KB-TK Anak Cerdas Ungaran adopts a Center-Based Learning model, which includes five centers: Preparation Center, Nature Center, Physical Arts Center, Block Center, and Role-Play Center. For learning assessment, KB-TK Anak Cerdas Ungaran employs several methods, including checklists, anecdotal records, children’s work products, and series photographs.